2015
DOI: 10.5114/aoms.2015.53307
|View full text |Cite
|
Sign up to set email alerts
|

Basic research In vitro antibacterial activity of seven Indian spices against high level gentamicin resistant strains of enterococci

Abstract: IntroductionThe aim of the study was to explore the in vitro antibacterial activity of seven ethanolic extracts of spices against high level gentamicin resistant (HLGR) enterococci isolated from human clinical samples.Material and methodsTwo hundred and fifteen enterococcal strains were isolated from clinical samples. High level gentamicin resistance in ethanolic extracts of cumin (Cuminum cyminum), cinnamon (Cinnamomum zeylanicum), ginger (Zingiber officinale), fenugreek (Trigonella foenum-graecum), cloves (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
(19 reference statements)
2
11
0
Order By: Relevance
“…The results from the agar disc diffusion method revealed that clove oil had inhibitory effects against all test MDR S. suis isolates. This is consistent with previous studies [33][34][35][36]. Incidentally, regarding the inhibition zones obtained from the essential oil, it is notable that differences can occur among studies due to the methods used in solubilizing the oils to obtain hydrophilic molecules [33], antimicrobial assays, and tested organisms.…”
Section: Discussionsupporting
confidence: 90%
“…The results from the agar disc diffusion method revealed that clove oil had inhibitory effects against all test MDR S. suis isolates. This is consistent with previous studies [33][34][35][36]. Incidentally, regarding the inhibition zones obtained from the essential oil, it is notable that differences can occur among studies due to the methods used in solubilizing the oils to obtain hydrophilic molecules [33], antimicrobial assays, and tested organisms.…”
Section: Discussionsupporting
confidence: 90%
“…Mandal et al reported that the DIZ value obtained from ethanol extracts (20 µL, 10 mg/mL) of cinnamon, clove, and cumin against methicillin-resistant S. aureus was in the range of 22–27 mm, 19–23 mm, and 9–15 mm, respectively [38]. Similarly, Revati et al found that high level gentamicin-resistant enterococci isolates were sensitive to ethanol extracts (50 µL, 100 mg/mL) of cinnamon, ginger, clove, and cumin, with the DIZ values of 31–34, 27–30, 25–26, and 19–20 mm, respectively [14]. Even though, most of the previous investigations were carried out with a limited number of antibiotic-resistant bacterial isolates as well as the tested spice samples, thus the broad antibacterial spectra of spice extracts could not be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have focused on the inhibitory effects of these spices on antibiotic-resistant bacteria. The methanolic and ethanolic extracts of cinnamon, which was the most studied spice, were reported to have inhibitory effects on high level gentamicin-resistant (HLGR) enterococci, multi-drug resistant Escherichia coli AG100, methicillin-resistant S. aureus (MRSA), as well as β-lactamase producing multi-drug Klebsiella pneumonia and Pseudomonas aeruginosa [14,15,16]. Moreover, the antibacterial properties of spices are mostly attributed to lipophilic essential oils in most previous studies [17].…”
Section: Introductionmentioning
confidence: 99%
“…rubra . Revati et al [ 77 ] explored the antimicrobial activities of seven Indian spice ethanol extracts against Enterococci (including 215 enterococcal strains) isolated from human clinical samples with the agar well diffusion method. Crude ethanol extract of cinnamon was the most effective against all the clinical isolates of Enterococci , with the DIZs ranging from 31 to 34 mm.…”
Section: Cinnamonmentioning
confidence: 99%